Fair trade information eliminates the positive brand effect: product choice behavior in Japan - Masaya Ota; Yusuke Sakata; Takao Iijima (Asian Journal of Sustainability and Social Responsibility (AJSSR), 2019)
We examine whether Fair Trade information affects the Japanese consumer's willingness to pay. We provide information on agroforestry and poverty resolution for chocolate products to test consumer behavior. We use an online survey and the Discrete Choice Experiment (DCE) method for hypothesis verification. The results show that brand has a positive effect on consumer willingness to pay, a negative effect in combination with agroforestry information, and no effect in combination with poverty resolution. In light of our results and discussions, to alleviate the above mentioned negative effect, we concluded that Japanese companies and universities should develop their corporate brand image along with their engagement in activities concerning Fair Trade and Japanese government should support to create their image to be engaged in activities concerning Fair Trade.
Keywords: 650; Ethical marketing; Ethical consumers; Choice experiment; Brand trust; Cause-related marketing